Innovation in transplantation: The digital era - Albino Eccher; Matteo Brunelli; Liron Pantanowitz; Anil Parwani; Ilaria Girolami; Aldo Scarpa (Elsevier, 2018)
The international symposium entitled "Innovation in Transplantation: The Digital Era" took place on June 7 and 8, 2018 in Verona, Italy. This meeting was borne out of the productive collaboration between the Universities and Hospital Trusts of Verona and Padua in Italy, in the context of a vast regional project called Research and innovation project within the Health Technology Assessment. The project aimed to create an innovative digital platform for teleconsultation and delivering diagnostic second opinions in the field of organ transplantation within the Veneto region. This conference brought together pathologists, health informatics leaders, clinicians, researchers, vendors, and health-care planners from all around the globe. The symposium was conceived to promote the exchange of knowledge and kindle fertile discussion among the 130 attendees from 15 different countries. This article conveys the highlights of this symposium.